Evaluasi Hasil Peledakan Overburden menggunakan Metode TOPSIS pada Tambang Terbuka PT Pamapersada Nusantara Jobsite TOPB Kalimantan Tengah - Auaradha Shukura Muji; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. Blasting is an important operations in mining. The explosion carried out by PT Pamapersada Nusantara Jobsite TOPB was an activity involving ANFO explosives. The improper selection of blasting geometry will create a problem with blasting results, such as rock fragmentation with a lot of boulders, flyrock, high ground vibrations, high air blasts, long digging time and high powder factor values. Based on the problems that arise, choosing the right blasting geometry will certainly be needed. Selecting the right blasting geometry can be done using the Multi Criteria Decision Making (MCDM). TOPSIS is one method that can be used in decision making. In determining the right geometry using this TOPSIS, safety and technical parameters are taken into consideration. Finally, Based on the blasting classification obtained from the average Ci* value of twenty available alternatives, the blasting results are categorized as good with a value 0.298 (class II). The most suitable blasting geometry for PT Pamapersada Nusantara Jobsite TOPB from evaluation using TOPSIS is a burden of 6.5 m, spacing of 7.5 m , drill hole diameter of 20 cm, subdrill of 0.5 m, hole depth of 7.25 m and stemming of 4.3 m.Keywords: Blasting, Blasting Geometry, Multi Criteria Decision Making (MCDM), Overburden, TOPSIS